Efek Pemberian Virgin Coconut Oil Dan Olive Oil Dalam Pakan Terhadap Pertumbuhan Tulang Femur Tikus Putih Jantan (Rattus norvegicus) - Suhartatik, S; Yuniwarti, Enny Yusuf Wachidah; Djaelani, Muhammad Anwar (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
This research aimed to annalyse the effects of virgin coconut oil and olive oil on the length, diameter and weight of the femur bone in white male rat (Rattus norvegicus). This research used 25 white male rats and consists of 5 treatments with 5 replications. This research used the treatment P0: as a control, P1: feed with an addition of 5 ml virgin coconut oil / kg feed, P2: feed with an addition of 10 ml virgin coconut oil / kg of feed, P3: feed with an addition of 5 ml olive oil / kg feed and P4: feed withÂ an addition of 10 ml olive oil / kg feed. This research used a method called Completely Randomized Design (CRD). The variables measured in this research are the weight, length and diameter of white male rats. The data was analyzed using Analysis of Variance (ANOVA) at 95% level. The results showed that the growth of femur bone in male rat does not have different response after giving virgin coconut oil and olive oil.Â Â